Prey for the Proteasome: Targeted Protein Degradation—A Medicinal Chemist's Perspective. Issue 36 (30th July 2020) - Luh, Laura M.; Scheib, Ulrike; Juenemann, Katrin; Wortmann, Lars; Brands, Michael; Cromm, Philipp M.
Abstract: Targeted protein degradation (TPD), the ability to control a proteins fate by triggering its degradation in a highly selective and effective manner, has created tremendous excitement in chemical biology and drug discovery within the past decades. The TPD field is spearheaded by small molecule induced protein degradation with molecular glues and proteolysis targeting chimeras (PROTACs) paving the way to expand the druggable space and to create a new paradigm in drug discovery. However, besides the therapeutic angle of TPD a plethora of novel techniques to modulate and control protein levels have been developed. This enables chemical biologists to better understand protein function and to discover and verify new therapeutic targets. This Review gives a comprehensive overview of chemical biology techniques inducing TPD. It explains the strengths and weaknesses of these methods in the context of drug discovery and discusses their future potential from a medicinal chemist's perspective. Abstract : Targeted protein degradation has created tremendous excitement in chemical biology and drug discovery. This Review gives a comprehensive overview of chemical biology tools as well as therapeutic approaches inducing targeted protein degradation and discusses them from a medicinal chemist's perspective.